Dietzia cinnamea: An increasingly recognized human pathogen. (2022) - Brown, William D.; Feinberg, Nina; Stedman, Eleanor; Dejace, Jean; Hale, Andrew J.
Abstract: The authors present the case of a bloodstream infection and sepsis due to Dietzia cinnamea in a severely malnourished patient with small bowel obstruction and pelvic abscess. The organism was identified with matrix-assisted laser desorption ionization-time-of-flight mass spectrometry. The authors discuss the characteristics, diagnosis, treatment, and emerging scope of clinical infection caused by Dietzia species.